(untitled) (Research, Society and Development, 2018)
The interpretive trail in urban forest can be considered an important means for the promotion of environmental education. The trail allows direct contact with the natural environment and for sharing scientific information on ecology local. The objective of this study was to report the results obtained from the environmental education project, “Interpretive trail in Funcesi’s campus”, developed in this institution of higher education. Participants were students and teachers from public and private schools in Itabira and nearby cities. Visitors were guided by monitors who instigated them to develop a new perception of the natural space through direct observation, questioning and tactile and visual sensibility. Between 2013 and 2017, 67 guided trails were conducted, and approximately 1952 people from 16 schools participated. 407 questionnaires were applied to the visitors to evaluate the satisfaction of the group at the end of the activity, with 83% evaluating the trail as "Very good". In addition to offering participants the opportunity to learn in the natural environment, the trail provided an exchange of knowledges and experiences among students, teachers and monitors of Funcesi.